2022
DOI: 10.1590/fst.16921
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some characteristic properties of Diyarbakir Orgu cheese produced by traditional and industrial method

Abstract: Orgu cheese, widely produced and consumed in Turkey's South-eastern Anatolia region, is usually made from sheep's milk. In this study, 15 traditional and 15 industrially produced Orgu cheese samples were compared in terms of chemical, biochemical, mineral content, antioxidant, and antimicrobial activity. While the mineral substance and antioxidant activity values of Orgu cheese samples produced by both traditional and industrial methods were close to each other, it was determined that there were differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…The average P concentration of cheese samples was determined as 148.49 mg/kg. This value was lower than the value obtained by Canozer (2020) for Orgu cheeses, Oksuztepe et al (2013) for Tulum and White cheeses, and Mattera et al (2016) for Pecorino d' Abruzzo cheese. Qin et al (2009) reported that Fe is to be transported to cheese through the machinery and tools used in the transport, storage, and processing of milk.…”
Section: Mineral Compositioncontrasting
confidence: 53%
“…The average P concentration of cheese samples was determined as 148.49 mg/kg. This value was lower than the value obtained by Canozer (2020) for Orgu cheeses, Oksuztepe et al (2013) for Tulum and White cheeses, and Mattera et al (2016) for Pecorino d' Abruzzo cheese. Qin et al (2009) reported that Fe is to be transported to cheese through the machinery and tools used in the transport, storage, and processing of milk.…”
Section: Mineral Compositioncontrasting
confidence: 53%
“…Cheese total polyphenols (mg of GAE4/100 g of cheese) were determined between 146.02 and 219.38 (mgGAE/100 g) (Giorgio et al, 2019). Canözer and Köse (2022) reported that the mean results of total phenol content and antioxidant activity value of Orgu cheeses were 811.14 mgGAE/kg and 5.17%, respectively. Results exhibited some fluctuations compared with literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Cheese total polyphenols (mg of GAE4/100 g of cheese) were determined between 146.02 and 219.38 (mgGAE/100 g) (Giorgio et al, 2019). Canözer and Köse (2022) reported that the mean results of total…”
Section: Bioactive Properties Of Outer and Inner Parts Of Blue-green ...mentioning
confidence: 99%
“…The acidity in milk and its products is expressed as the total value of acidity formed as a result of citrate, phosphate, albumin, globulin, and carbon dioxide found in the nature of milk, as well as microorganism and culture activities (Canozer & Köse, 2022). Acidity is one of the important parameters that affect the quality of milk and its products and must be controlled during the production phase and the storage period.…”
Section: Resultsmentioning
confidence: 99%